OPTIMALISASI GIZI BAYI DAN BALITA MELALUI PEMBERDAYAAN KELUARGA (NUTRITION OPTIMIZATION OF INFANTS AND CHILDREN THROUGH FAMILY EMPOWERMENT IN THE UTILIZATION OF MCH BOOKS IN SURABAYA)DALAM PEMANFATAN BUKU KIA DI SURABAYA - Rekawati Susilaningrum (Pusat Penelitian dan Pengabdian Masyarakat Poltekkes Kemenkes Surabaya, 2022)
Background. In Surabaya, the percentage of children under five with BGM is around 0.6%. Meanwhile, there are around 0.2% malnourished children under five (East Java Province Health Office, 2017). This percentage is relatively low, but health workers must remain vigilant, namely by continuing to weigh children regularly. There are several health centers in Surabaya, which have not met the target for the number of children under five being weighed (Dinkes, 2018). If parents do not provide adequate nutrition, children can experience nutritional disorders. For this reason, mothers need to understand how to provide proper nutrition as in the KIA book. Based on the 2018 Riskesdas data, the proportion of KIA book ownership is above 80% (Kemenkes RI, 2018). The use of the MCH handbook does not directly reduce maternal and child mortality rates. However, with the use of the KIA book, mothers and families can increase preventive and promotional efforts on health problems (Kemenkes RI, 2016a). One of the real activities is community empowerment in the use of the MCH handbook. For that we need an active role of the family, especially mothers. The aim of this community service is to increase the use of MCH books through training in an effort to optimize the fulfillment of nutrition for infants and toddlers. Methods. The methods used in this community service activity are interviews, examinations and counseling. The target audience is families (mothers) who have children under five. The target number is 30 families. Result. There were 83% of children with normal nutritional status, 13% of them were classified as thin. There were 37% of children given food before 6 months of age, 60% of children given formula milk before 6 months of age. There are 47% of children having difficulty eating. About 87% of mothers try to cook their own food for their children. The results of the pre test and post test showed an increase in knowledge, positive attitudes and appropriate actions towards the use of the KIA book. Keywords:Optimization, Nutrition, Empowerment, KIA book